Characteristics and outcomes of older HIV-infected patients receiving antiretroviral therapy in Malawi: A retrospective observation cohort study - Tweya, Hannock (PLoS One, 2017)
OBJECTIVE: To estimate patients enrolling on antiretroviral therapy (ART) over time; describe trends in baseline characteristics; and compare immunological response, loss to follow-up (LTFU), and mortality by three age groups (25–39, 40–49 and ≥50 years). DESIGN: A retrospective observation cohort study. METHODS: This study used routine ART data from two public clinics in Lilongwe, Malawi. All HIV-infected individuals, except pregnant or breastfeeding women, aged ≥ 25 years at ART initiation between 2006 and 2015 were included. Poisson regression models estimated risk of mortality, stratified by age groups. RESULTS: Of 37,378 ART patients, 3,406 were ≥ 50 years old. Patients aged ≥ 50 years initiated ART with more advanced WHO clinical stage and lower CD4 cell count than their younger counterparts. Older patients had a significantly slower immunological response to ART in the first 18 months on ART compared to patients aged 25–39 years (p = 0.04). Overall mortality rates were 2.3 (95% confidence Interval (CI) 2.2–2.4), 2.9 (95% CI 2.7–3.2) and 4.6 (95% CI 4.2–5.1) per 100 person-years in patients aged 25–39 years, 40–49 years and 50 years and older, respectively. Overall LTFU rates were 6.3 (95% CI 6.1–6.5), 4.5 (95% CI 4.2–4.7), and 5.6 (95% CI 5.1–6.1) per 100 person years among increasing age cohorts. The proportion of patients aged ≥ 50 years and newly enrolling into ART care remained stable at 9% while the proportion of active ART patients aged ≥50 years increased from 10% in 2006 to 15% in 2015. CONCLUSION: Older people had slower immunological response and higher mortality. Malawi appears to be undergoing a demographic shift in people living with HIV. Increased consideration of long-term ART-related problems, drug-drug interactions and age-related non-communicable diseases is warranted.